2021
DOI: 10.3892/ijmm.2021.4936
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of chloroacetamide herbicides and their metabolites in vitro and in vivo

Abstract: The toxicity of chloroacetamide herbicide in embryo development remains unclear. Acetochlor (AC) is a chloroacetamide that metabolizes into 2-ethyl-6-methyl-2-chloroacetanilide (CMEPA) and 6-ethyl-o-toluidine (MEA). The present study determined the potential effect of AC and its metabolites on embryo development. Both HepG2 cells and zebrafish embryos were exposed to AC, CMEPA and MEA in the presence or absence of co-treatment with anti-reactive oxygen species (ROS) reagent N-acetylcysteine. The generation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The residual concentrations of acetochlor and its metabolite occurrence in aquatic ecosystems may induce adverse effects in non-target aquatic organisms. For example, acetochlor affects thyroid hormone levels [ 34 , 35 , 36 ], oxidative stress [ 37 , 38 ], antioxidant enzymes levels [ 39 , 40 ], histology [ 39 , 41 ], early development [ 34 , 35 , 37 , 39 , 42 ], immune system [ 42 ], and behaviour [ 38 , 41 ]. Moreover, acetochlor can be accumulated in organisms, posing a risk to the entire ecosystem through the food web [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The residual concentrations of acetochlor and its metabolite occurrence in aquatic ecosystems may induce adverse effects in non-target aquatic organisms. For example, acetochlor affects thyroid hormone levels [ 34 , 35 , 36 ], oxidative stress [ 37 , 38 ], antioxidant enzymes levels [ 39 , 40 ], histology [ 39 , 41 ], early development [ 34 , 35 , 37 , 39 , 42 ], immune system [ 42 ], and behaviour [ 38 , 41 ]. Moreover, acetochlor can be accumulated in organisms, posing a risk to the entire ecosystem through the food web [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al. showed chloroacetanilides can increase oxidative stress by increasing reactive oxygen species level and trigger apoptosis [ 21 ]. Studies also showed that utilization of chloroacetanilides links to caner and Parkinson's disease [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%